Farmland Challenges in the Haor Basin of Bangladesh: Nature and Solutions - Shovon Roy (Turkish Journal of Agriculture: Food Science and Technology)
Haor regions are inhabited by one of the most economically disadvantaged communities, which rely on agriculture and endure numerous challenges due to its vulnerability. This article analyzes the data obtained from Key Informant Interviews (KIIs) and Focus Group Discussions (FGDs), which were subsequently connected to prior publications to identify the nature of the agricultural land-related problems in the Netrokona Haor basin. Multiple concerns and their nature have been uncovered through the examination. Among those, difficulties in irrigation systems pose the greatest challenge for regional producers. Additional challenges encompass land fragmentation, pollution, erosion, fishing-related concerns, drainage infrastructure, and flood. This study discusses probable solutions with the directive to new research that claims collaborative venture through government and private agencies. Carefully designed research-based policy framework prioritizing strict implementation of existing laws is crucial to effectively mitigate the problem.